Full-length RNA sequencing reveals the mechanisms by which an TSWV–HCRV complex suppresses plant basal resistance - Gui, Min; Hu, Huaran; Jia, Zhiqiang; Gao, Xue; Tao, Hongzheng; Li, Yongzhong; Liu, Yating (Frontiers in Plant Science, 2023)
Viruses deploy numerous strategies to infect plants, typically by forming a complex with another virus, which leads to more efficient infection. However, the detailed plant responses to viral infection and the underlying mechanisms of co-infection mechanisms still remained unclear. Previously, we found that Tomato spotted wilt orthotospovirus (TSWV) and Hippeastrum chlorotic ringspot orthotospovirus (HCRV) could infect plants in the field by forming a complex. In this study, we found that TSWV infected Nicotiana benthamiana (N. benthamiana) plants in cooperation with HCRV, leading to a more efficient infection rate of both viruses. We then used the in-depth full-length transcriptome to analyze the responses of N. benthamiana to complex infection by TSWV-HCRV. We found that infection of the individual TSWV and HCRV triggered plant defense responses, including the jasmonic acid signaling pathway, autophagy and secondary metabolism. However, TSWV-HCRV co-infection could not trigger and even suppressed some genes that are involved in these basal resistance responses, suggested that co-infection is advantageous for the virus not for the plants. Typically, TSWV-HCRV complex inhibited the NbPR1 expression to suppress N. benthamiana resistance. Moreover, the TSWV-HCRV complex could alter the expression of microRNAs (miRNAs), especially novel-m0782-3p and miR1992-3p, which directly interact with NbSAM and NbWRKY6 and suppressed their expression in N. benthamiana, leading downregulation of NbPR1 and loss of resistance in N. benthamiana to TSWV and HCRV viruses, then promote their successful infection in plant tissue. Overall, our results elucidated the co-infection mechanisms of TSWV-HCRV in N. benthamiana through deploying the miRNA of plants to suppress plant basal resistance and contributed to develop a novel strategy to control crop disease caused by this virus complex.